2016
DOI: 10.1136/bmj.h6420
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Enterobacteriaceae: mechanisms and clinical implications

Abstract: Resistance of the Enterobacteriaceae to antibiotics, especially of the β lactam type, is increasingly dominated by the mobilization of continuously expressed single genes that encode efficient drug modifying enzymes. Strong and ubiquitous selection pressure has seemingly been accompanied by a shift from "natural" resistance, such as inducible chromosomal enzymes, membrane impermeability, and drug efflux, to the modern paradigm of mobile gene pools that largely determine the epidemiology of modern antibiotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(204 citation statements)
references
References 251 publications
(171 reference statements)
3
193
0
8
Order By: Relevance
“…The dissemination of and mechanisms of resistance by ESBLs and carbapenemases in K. pneumoniae and other bacteria are not the focus of this review, so we refer readers to the other excellent reviews (11,25). Here, however, we briefly summarize some of the major mechanisms of drug resistance found in K. pneumoniae.…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissemination of and mechanisms of resistance by ESBLs and carbapenemases in K. pneumoniae and other bacteria are not the focus of this review, so we refer readers to the other excellent reviews (11,25). Here, however, we briefly summarize some of the major mechanisms of drug resistance found in K. pneumoniae.…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
“…It requires the carriage of these carbapenem resistance genes but often also requires the carriage of other ␤-lactamases and/or mutations in outer membrane proteins (OMPs) that render the bacteria more resistant to ␤-lactams, particularly in combination with the expression of a carbapenemase (10,31). ESBLs, which are also found worldwide, can also be caused by a number of ␤-lactamases, the most common of which are TEM, SHV, CTX-M, and OXA (11,25).…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
“…This became more serious in case of Gram-negative bacteria such as A. baumannii, E. coli and P. aeruginosa and Gram-positive S. aureus which were associated with pus and wound infections, due to extensive prescription and inadequate dose of antibiotics (Rice, 2006, Misic et al, 2014. Rapid spread of multidrug resistant bacteria poses a serious threat to public health due to the limited treatment options and the decrease in the discovery of new classes of antibiotics (Iredell et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance is more available now to organisms like E.coli. [26] The problems further worsen due to wrong management of the infection and/or over treatment. [13] Another revealing study showed 96% (4% gram positives) of total isolated microbes from UTI cases to be gram negative bacteria, among which E.coli was most prevalent.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%